The Influence of Transformational Leadership and Organizational Culture on The Performance and Motivation of Aceh Brimob Personnel - Beridiansyah, Beridiansyah; Adam, Muhammad; Yunus, Mukhlis (Pelopor Publikasi Akademika, 2023)
This research aims to investigate the influence of transformational leadership on personnel performance and work motivation, the impact of transformational organizational culture on personnel performance and work motivation, the influence of transformational leadership on personnel loyalty, the influence of organizational culture on personnel loyalty, the relationship between personnel performance and personnel loyalty, and the relationship between work motivation and personnel loyalty. The research also aims to explore the influence of transformational leadership on personnel loyalty through personnel performance and work motivation, as well as the influence of organizational culture on personnel loyalty through personnel performance and work motivation in the Brimob Unit of the Aceh Regional Police. The research was conducted at the Brimob Unit of the Aceh Regional Police with a sample of 300 respondents selected using purposive random sampling technique. The research findings indicate that there is a significant influence of transformational leadership and organizational culture on personnel performance and work motivation. Furthermore, there is a significant influence of transformational leadership and organizational culture on personnel loyalty. Additionally, intrinsic work motivation and work motivation have a significant influence on personnel loyalty. There is a direct influence of transformational leadership on personnel loyalty through work motivation, as well as an indirect influence of transformational leadership on personnel loyalty through personnel performance. Similarly, there is a direct influence of organizational culture on personnel loyalty through personnel performance, and an indirect influence of organizational culture on personnel loyalty through work motivation.